Effects of warming and isolation from precipitation on the soil carbon, nitrogen, and phosphorus, and their stoichiometries in an alpine meadow in the Qinghai–Tibet Plateau: A greenhouse warming study - Tong, Yongpeng; Long, Yanjun; Yang, Zhen’an (Frontiers in Ecology and Evolution, 2023)
In the Qinghai–Tibet Plateau (QTP), alpine meadows are among the most noticeable reflection of global climate change. However, effects of global warming on soils hosting alpine meadows in the QTP, such as reduced moisture because of low precipitation, remain unclear. Methods: Thus here, the soil moisture content (SMC), pH, dissolved organic carbon (DOC), ammonium nitrogen (NH4+–N), nitrate nitrogen (NO3−–N) and available phosphorus (AP) contents in the QTP were analyzed. The changes in and stoichiometries of total carbon, nitrogen, and phosphorus (TC, TN, and TP), microbial biomass carbon, nitrogen, and phosphorus (MBC, MBN, and MBP), β-1,4-glucosidase (BG), β-1,4-N-acetylglucoaminosidase (NAG), leucine aminopeptidase (LAP), and acid phosphatase (ACP) in the 0–30 cm layer of soils associated with warming in a greenhouse in the QTP from 2015-2020 were characterized. Results: We found that warming in the greenhouse significantly decreased the SMC, NO3−–N, MBC, MBN, MBP, BG, LAP, ACP, and enzymatic C:N ratio. The warming increased the DOC, NH4+–N, AP, MBC:MBN, and enzymatic N:P ratios noticeably. The pH, TC, TN, TP, C:N, C:P, N:P, MBC:MBP, MBN:MBP, and enzymatic C:P ratios were minimally affected. Conclusion: The results also show that that warming and isolation from precipitation promoted mineralization of N and P in the soil, but microorganisms limitedly benefited directly from the enhanced nutrient availability under the prevailing conditions.